2014
DOI: 10.1111/ejh.12268
|View full text |Cite
|
Sign up to set email alerts
|

F‐18 FDG PET/CT quantization parameters as predictors of outcome in patients with diffuse large B‐cell lymphoma

Abstract: Despite the availability of new tools for the quantitative assessment of disease activity on PET/CT, the SUVmax rather than MTV and TLG remains the only predictor for EFS in DLBCL patients. The magnitude of glycolytic activity rather than the amount of metabolically active burden holds a predominant value for determining the response to chemotherapy in DLBCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
78
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 37 publications
(41 reference statements)
1
78
2
1
Order By: Relevance
“…[27][28][29][30] Among these functional parameters, TLG appears of particular interest as a prognostic pointer in DLBCL. 27,[31][32][33][34][35] However, no specific study has so far addressed PMBCL as a distinct subtype [2][3][4][5][6] in which the metabolic response rate appears clearly inferior to that seen in other DLBCLs and Hodgkin lymphoma. 7,8,36 Although the overall results of treatment of PMBCL are favorable, 7,8 there remains a clear minority in whom the initial treatment fails, following which second-line treatment is frequently unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29][30] Among these functional parameters, TLG appears of particular interest as a prognostic pointer in DLBCL. 27,[31][32][33][34][35] However, no specific study has so far addressed PMBCL as a distinct subtype [2][3][4][5][6] in which the metabolic response rate appears clearly inferior to that seen in other DLBCLs and Hodgkin lymphoma. 7,8,36 Although the overall results of treatment of PMBCL are favorable, 7,8 there remains a clear minority in whom the initial treatment fails, following which second-line treatment is frequently unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…Different methods and a wide range of threshold levels have been proposed to calculate the volume-based PET parameters either in solid tumors or in different subtypes of lymphoma (mainly DLBCL). [25][26][27][28][29][30][31][32][33][34][35][42][43][44][45] Moreover, there are no published technical references about the methodology for the calculation of the volumebased PET parameters and definition of specific cutoff values in PMBCL.…”
Section: Discussionmentioning
confidence: 99%
“…SUVmax was a predictor of survival. 65,66 One study did not find a predictive value for TLG, 66 whereas the other study did. 65 High MTV was a better predictor of survival than SUVmax in 165 patients with Ann Arbor stage IE or IIE primary gastrointestinal DLBCL and was an independent prognostic factor for PFS and OS in multivariate analysis.…”
mentioning
confidence: 98%
“…In aggressive B-cell lymphoma (DLBCL), multiple retrospective studies investigated pretreatment PET-derived volumetrics as a potential predictor of survival in patients undergoing R-CHOP therapy (5)(6)(7)(8)(9). A systematic review of 7 retrospective DLBCL studies (n 5 703) suggested that both SUV max and MTV were significant prognostic factors for PFS (P 5 0.038 and 0.000, respectively) (5).…”
mentioning
confidence: 99%
“…These summarized studies used different segmentation techniques varying from fixed-threshold methods based on absolute SUV max (8) or percentage thresholding using 25% (11), 37% (9), 40% (10), 41% (1), or 42% of the SUV max (7). This methodologic variability resulted in widely disparate cutoff values ranging from 11 to 30 for SUV max , from 130 to 550 mL for MTV, and from 415 to 2,955 for TLG in the prediction survival in various lymphoma subtypes.…”
mentioning
confidence: 99%